Characterization of the Antigenic and Immunogenic Properties of the Gametocyte Antigen 56 from Eimeria necatrix - Feiyan Wang; Liqin Cao; Lele Wang; Jinjun Xu; Jianping Tao; Dandan Liu (Animals, 2025)
Coccidiosis, caused by Eimeria spp., significantly reduces poultry productivity and causes major economic losses. Traditional control methods are limited by drug resistance and high production costs. Recent genomic and bioinformatic advances have enabled the identification of novel antigens, making recombinant subunit vaccines a promising next-generation strategy by eliciting robust cellular and humoral immune responses. This study investigates the E. necatrix gametocyte protein 56 (EnGAM56) as a potential candidate for recombinant subunit vaccines. The full-length E. necatrix gametocyte gam56 gene (Engam56-F) was amplified, expressed in vitro, and characterized via SDS-PAGE and Western blot. Immunofluorescence assays revealed that EnGAM56-F is specifically localized in gametocytes and unsporulated oocysts. Chickens immunized with recombinant proteins (rEnGAM56-F and rEnGAM56-T) were evaluated for immunoprotection against E. necatrix infection through lesion scores, weight gain, oocyst production, anticoccidial index (ACI), and antibody and cytokine levels. The synergistic effects were evaluated by employing various combinations of recombinant proteins, including rEtGAM22, rEtGAM56-T, and rEtGAM59. Results showed that EnGAM56-F encodes a 468-amino acid protein with distinct tyrosine-serine-rich and proline-methionine-rich regions. rEnGAM56-F was specifically recognized by both anti-6 × His tag antibodies and convalescent serum from chickens infected with E. necatrix. Both rEnGAM56-F and rEnGAM56-T provided immune protection, with rEnGAM56-T showing superior efficacy. The combination of rEnGAM (22 + 59 + 56-T) yielded the strongest immune response, followed by rEnGAM (22 + 56-T). These findings highlight the potential of EnGAM56 as a candidate for recombinant subunit anticoccidial vaccines.